THE ANALYSIS ON STUDENTS’ MATHEMATICS LEARNING DIFFICULTIES VIEWED FROM THEIR SELF-EFFICACY IN GRADE VIII ON SMP MUHAMMADIYAH NGEMPLAK SLEMAN REGENCY IN THE ACADEMIC YEAR OF 2018/2019 - Gity Oktaviani; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2021)
The difficulty of learning mathematics is still experienced by students in grade VIII SMP Muhammadiyah Ngemplak. This research aims to explain the difficulties of learning mathematics that is reviewed from the efficacy of self-esteem in grade VIII students of SMP Muhammadiyah Ngemplak. This research uses qualitative research methods. The subject of this study was 9 students of grade VIII A SMP Muhammadiyah Ngemplak year 2018/2019. Object research is the difficulty of learning mathematics reviewed from self-efficacy. The data collection techniques consist of polls, tests, documentation. The research instrument is a self-efficacy poll sheet, a math test sheet, an interview guideline, an interview recorder, and a field record. Validity of data using source triangulation. Data analysis using data reduction, data presentation, and withdrawal of conclusions. The results showed students who have difficulty studying mathematics factually 87.88%, students who have difficulty learning mathematics conceptually 41.41%, and students who have difficulty learning mathematics procedurally 25.25%. The factors that cause mathematics learning difficulties consist of 3 parts, among others: difficulty learning mathematics reviewed from self-efficacy with the magnitude aspect is the student is hard to memorize mathematical formulas. The difficulty of learning mathematics is reviewed from the self-efficacy with the strength aspect is the students are less confident and cheating the answers of friends. The difficulty of learning mathematics is reviewed from the efficacy of the generality with the aspect of the students always see an example of the problem when working on mathematical tasks.